Penentuan Lot Size Pemesanan Bahan Baku Dengan Batasan Kapasitas Gudang - Dana Marsetiya Utama (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2016)
This paper explains the problem of determining the lot size of ordering raw materials with warehouse capacity limitation in order to minimize inventory costs. Generally, the lot size of ordering raw materials determined without considering warehouse capacity. The algorithm that used is Wagner Within (WW) which is modified by adding a warehouse capacity as a constraint. The result shows the minimum of total inventory cost is 24,100 and the ordering raw materials at the week 3, 5 and 7.